2010
DOI: 10.3945/jn.110.121483
|View full text |Cite
|
Sign up to set email alerts
|

NHANES Monitoring of Serum 25-Hydroxyvitamin D: A Roundtable Summary

Abstract: A roundtable to discuss monitoring of serum 25-hydroxyvitamin D [25(OH)D] in the NHANES was held in late July 2009. Topics included the following: 1) options for dealing with assay fluctuations in serum 25(OH)D in the NHANES conducted between 1988 and 2006; 2) approaches for transitioning between the RIA used in the NHANES between 1988 and 2006 to the liquid chromatography tandem MS (LC-MS/MS) measurement procedure to be used in NHANES 2007 and later; 3) approaches for integrating the recently available standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
103
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(104 citation statements)
references
References 20 publications
0
103
1
Order By: Relevance
“…Areal bone mineral density (BMD) of the femoral neck area was measured using dual energy X-ray absorptiometry [24]. Furthermore, blood samples were taken and serum vitamin D levels examined by radioimmunoassay [49].…”
Section: Measurements and Proceduresmentioning
confidence: 99%
“…Areal bone mineral density (BMD) of the femoral neck area was measured using dual energy X-ray absorptiometry [24]. Furthermore, blood samples were taken and serum vitamin D levels examined by radioimmunoassay [49].…”
Section: Measurements and Proceduresmentioning
confidence: 99%
“…This interference is only problematic for LC-MS/MS methodology, since the mass spectrometers cannot distinguish stereoisomers (35), and can potentially result in overestimation of 25-OHD 3 . None of the main immunoassays in use today are susceptible to 3-epi-25-OHD 3 interference (14). Although the amounts of vitamin D epimer in adult serum are generally small, high concentrations have been reported in some individuals (36).…”
Section: Choice Of Methodsmentioning
confidence: 99%
“…Ginde et al [4] [40] reported that there was a change in the DioSorin RIA kits used over 1988-2004 because during the later years a new antibody with improved binding was introduced and detergents were added to a buffer to reduce nonspecific binding. They [40] also reported that to obtain corrected values for 1988-1994, they be multiplied by 0.8429.…”
Section: Introductionmentioning
confidence: 99%
“…They [40] also reported that to obtain corrected values for 1988-1994, they be multiplied by 0.8429. If that was to be so, reported mean of 30 ng/mL for 1988-1994 will be corrected to 25.2 ng/mL or just about the same as for 2001-2004.…”
Section: Introductionmentioning
confidence: 99%